The Synthesis, Characterization and Electrochemical Behavior of Transition Metal Complexes Containing Nitrogen Heterocyclic Sulphur Donor Ligand - Gorgulu, Ahmet Orhan; Celikkan, Hueseyin; Arslan, Mustafa (Slovensko Kemijsko Drustvo, 2009)
1,3-di(2-methylpiperidino)propan-2-ol (ROH) was synthesized 1,3-dichloropropan-2-ol with 2-methlypiperidine. Potassium 1,3-di(2-methylpiperidino)propan-2-O-xanthate (ROCSSK) was obtained from the reaction of 1,3-di(2-methylpiperidino)propan-2-ol (ROH) with carbon disulfide and metallic potassium. All products were generally obtained in high yields. xanthate complexes of Co(II), Ni(II) and Cu(I) was synthesized in the medium water as [CoL2(H2O)(2)], [NiL2(H2O)(2)]center dot 2H(2)O and [CuL]center dot 2H(2)O. The novel xanthate ligand and its complexes were defined by FT-IR, H-1 and C-13 NMR spectroscopies, elemental analyses, magnetic susceptibility and TGA techniques. [CoL2(H2O)(2)] and [NiL2(H2O)(2)]center dot H2O complexes were subjected to cyclic voltammetry using Pt working electrode and Ag/AgCl (3 M KCl) reference electrode.
Keywords: Co(II); Ni(II) and Cu(I) complexes; xanthate; cyclic voltammetry